Art in Tanzania 2000. - National Museum Dar es Salaam; East African Movies, Dar es Salaam; Goscinny, Yves; Jengo, Elias; Kayombo, N.A.; Mandawa, Doreen; Merinyo; Siege, Nasrin (Dar-es-Salaam : East African Movies Ltd., 2000)
Abdallah, Saidi ; Amonde, Omary ; Anagangola, Abumuwasi ; Bush, Mikidadi ; Casmiro, Salvador ; Chilonga, Haji ; Costales, Miguel ; Dastani, Nyedi ; Dastani, Simuni ; Dula, Boute ; Flo ; Hamedi, Athumani ; Jengo, Elias Elieza ; Job, John Lulandala ; Kipanya, Masoud ; Kyando, David ; Laurent, Véronique ; Lilanga, George ; Lilanga, Hemrick John ; Mandawa, Doreen May ; Mantheakis, Stella ; Martin, Peter ; Mayige, Petro Paulo ; Merinyo ; Msagula, Damian ; Rashidi, Sey ; Raza, Mohamed ; Sulemanji, Muzu ; Y.G. ; Yengi, Poni
biog. per kunstenaar
Engels
Art in Tanzania 2000, National Museum Dar-es-Salaam / East African Movies, Dar-es-Salaam, 01.12 - 20.12.2000
boek
Keywords: Tanzania